DETERMINANT OF EMPLOYES PERFORMANCE (Case of South of Sulawesi) - Abdul Hafid Burhami (Salewangang Institut Publishing, 2018)
Performance is one of the tools to measure negligence in managing human resources in one organization. Leadership and discipline are two things that affect performance. This study aims to determine the factors that influence employee performance. The analytical method used in this study is descriptive and multiple regression. The results showed that leadership and discipline had an effect on performance, but the effect was very small at only 0.396 percent.